Nauczyciel wczesnej edukacji w obliczu utopijnych wyobrażeń matek. Ku teorii ugruntowanej - Szkolak-Stępień, Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The article addresses the problem of mother model reconstruction of an early childhood education teacher using a qualitative research strategy (grounded theory of the studied phenomenon). As a result of research it was possible to formulate a research hypothesis that brings closer the grounded theory in context and as interpretation of specific process. It also enabled to create a portrait of a “perfect” an early childhood education teacher (a teacher-master) in the grass-roots, utopian perspective of mothers.
Keywords: early childhood education teachers; imaginations of mothers; grounded theory